A algorithm of fast digital phase modulation signal recognition - Qu Jun-suo (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Classifications of digital modulation, the signal characteristics of the phase of the cycle will cause the phase wrapped and reduce overlapping signals in the received RF digital modulation automatically correct classification probability. According to the principle of minimum mean square, a phase modulation and phase modulation signal classification features as well as 2PSK and MPSK classification. The experiments illustrate the robust of the feature-based approach for automatic digital modulation classification and a higher recognition probability suitable to various pulse shaping filters, roll-off factors and symbol rates.DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1666